Resultados de la esofaguectomía mínimamente invasiva por cáncer de esófago a medio y largo plazo. - Forneiro Pérez, Rocío; Ubiña Martínez, Juan Alfredo; Lendínez Romero, Inmaculada (Revista de Cirugia, 2024)
Introduction: Oesophagectomy is currently the curative treatment for oesophageal cancer. The aim of this study is to know the results of minimally invasive oesophagectomy in the short and medium term in patients operated on for squamous cell carcinoma and adenocarcinoma of the oesophagus in our hospital. Material and Methods: 19 patients were collected from January 2020 to June 2021 and all of them were followed up for 20 months. Different variables related to the patient, tumour, surgery and postoperative period were collected. Data were stored and processed using R-Comander statistical software assuming an α-error of 0.05. Results: The median total hospital stay was 29 days. Six patients required readmission to resuscitation: two for septic shock secondary to grade III anastomotic leak, one for upper gastrointestinal haemorrhage and three for respiratory failure. At 90 days, 5.3% of the total number of patients were readmitted. There were no deaths in the three months following surgery. All patients had a survival of more than six months. Overall survival at six, 12 and 18 months was 100, 84 and 63%. Disease-free survival at three months was 84%, at six months 63% and at one year 58%. Discussion: The results obtained in our study coincide with those reported in the literature. Minimally invasive oesophagectomy is therefore an effective technique in the treatment of oesophageal cancer